Helter skelter : the true story of the Manson murders - Bugliosi, Vincent; Gentry, Curt, 1931-2014 (New York : W.W. Norton, 2001)
The #1 bestselling true crime book ever, this revised edition tells what really happened in the murders carried out by the Manson family. Taking a look at the man, the method and the madness, the book now features a new Afterword. of photos.
The murders -- The killers -- The investigation -- Phase two -- The search for the motive --'Don't you know who you're crucifying?' -- The trial -- Murder in the wind -- Fires in your cities.
Includes index.
Keywords: Manson, Charles, -- 1934-; Murder -- California -- Case studies